THE IMPLEMENTATION OF PERSONALISED LEARNING TO HELP STUDENTS IMPROVE THE LISTENING SKILL - Soerianingrat, Nyi Raden Alifa Mariani Saleha (2016)
The listening skill is a part of the English national examination (UN), and about 40% of students think that it is a hard skill to master. Thus there should be a way to help them master the skill. The aim of this study was to see if the implementation of personalised learning could help students improve their listening skill, as well as the steps of implementation and the students' perceptions about it. About 48 freshmen were taken as the samples of this study. This quasi-experimental research was employed with a pre-test, a post-test, questionnaires and written documents as the research instruments. This study was conducted based on the five key features of personalised learning as mentioned by O'Donoghue namely 1) Ensure every learner is as active as possible; 2) Design frequent formative assessment; 3) Put the emphasis on peers learning together; 4) Consider whether learning tasks can be personalised; and 5) Consider how technology can help. Based on the research, it is found that personalised learning can improve the students' listening score, and help them to feel happier when they are studying. The students also like it when they can have more voice and choice in the classroom. Thus, it is suggested to use personalised learning to teach EFL, especially to teach listening.; Kemampuan menyimak adalah salah satu bagian dari ujian nasional (UN) bahasa Inggris dan sekitar 40% dari siswa menyatakan kemampuan ini adalah kemampuan yang sulit dipelajari. Oleh karenanya, harus ada cara untuk bisa membantu mereka mempelajari hal ini. Tujuan dari studi ini adalah untuk melihat jika implementasi dari personalised learning bisa membantu siswa memperbaiki kemampuan menyimak mereka, bagaimana cara pengimplementasiannya dan persepsi siswa terhadap implementasi ini. Sekitar 48 mahasiswa baru diambil sebagai sampel studi. Studi ini menggunakan quasi-experimental dengan pre-tes, pos-tes, kuesioner dan dokumen tertulis. Studi ini dilakukan berdasarkan lima fitur yang disebutkan oleh O'Donoghue yaitu 1) pastikan semua siswa seaktif mungkin; 2) desain penilaian formative berkala; 3) letakan perhatian pada kerja sama siswa; 4) pertimbangkan jika tugas-tugas belajar bisa dipersonalisasi; dan 5) pertimbangkan bagaimana teknologi bisa membantu. Berdasarkan studi ini, ditemukan bahwa personalised learning bisa menaikkan nilai menyimak siswa dan membantu mereka merasa lebih senang ketika belajar. Mereka juga suka ketika mereka bisa memiliki lebih banyak suara dan pendapat di ruangan kelas. Oleh karena itu, personalised learning dianjurkan untuk digunakan di dalam pengajaran EFL, terutama untuk mengajarkan menyimak.